Green Manufacturing of Rutile (TiO2) Welding Electrodes with Blast Furnace Slag - Kaptanoglu, Mustafa (Mdpi, 2025)
This study develops a sustainable welding approach by incorporating 35-50% blast furnace slag (BFS), a byproduct of the steel industry, into rutile-type electrode coatings. To fabricate the electrodes, BFS was dry-mixed with fluxes, followed by the addition of potassium silicate binder to create a paste. This mixture was then pressed onto 3.25 mm core wires at 150 bar and heat-treated at 150 degrees C for two hours. Weld quality and performance were evaluated through visual inspections, microstructure and XRD analyses, hardness, tensile, and impact tests. Visual inspections confirmed weld quality comparable to commercial standards, with stable arc and minimal spatter. Microstructure analysis revealed a ferrite-dominated weld metal with TiO2 and FeTiO3 phases in the slag layer, enhancing strength and toughness. Electrodes with 35-40% BFS achieved yield strength of 477-482 MPa, tensile strength of 570-573 MPa, and impact energy of 58-59 J at 0 degrees C, complying with ISO 2560:2020. BFS integration reduced CO2 emissions by 0.28-0.4 kg per kg of coating and diverted 200-600 kg of slag per ton of steel from landfills. Coating and raw material costs decreased by 33-48% and 15-25%, respectively, aligning with the EU Green Deal's circular economy goals and enhancing weld quality and sustainability.
Keywords: green manufacturing; blast furnace slag; rutile (TiO2) electrode coatings; sustainable welding; circular economy